2022
DOI: 10.1002/ese3.1326
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of heat pump dryers for drying agricultural products

Abstract: Fruits and vegetables are agricultural products that require preservation to enhance and protect shelf life, encapsulate natural flavour, and retain nutritional content. Globally, agricultural products are preserved by a range of means, the most prevalent of which is the heat pump dryer, which produces the best results even in unfavourable climatic conditions. Heat pump dryers come in different types and their performance varies depending on the type. This study aims to evaluate recently developed heat pump dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 112 publications
(209 reference statements)
6
5
0
Order By: Relevance
“…The SMER of 1.33 kg/kWh in this study is within the range of 0.156–9.25 kg/kWh reported by Loemba et al. ( 2022 ) for most of the heat pump dryers. The COP was calculated from Equation 8 and found to be 3.4, and the thermal efficiency was calculated from Equation 9 and found to be 54.0%.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The SMER of 1.33 kg/kWh in this study is within the range of 0.156–9.25 kg/kWh reported by Loemba et al. ( 2022 ) for most of the heat pump dryers. The COP was calculated from Equation 8 and found to be 3.4, and the thermal efficiency was calculated from Equation 9 and found to be 54.0%.…”
Section: Resultssupporting
confidence: 86%
“…The COP was calculated from Equation 8 and found to be 3.4, and the thermal efficiency was calculated from Equation 9and found to be 54.0%. The COP obtained from this study is within the range reported by Loemba et al (2022) during the compressive assessment of heat pumps for agricultural products, in which it was reported that most of the heat pumps have COPs ranging from 1.94 to 5.38. The thermal efficiency of SAHPD obtained in this study is in agreement with the 56.69% reported by Singh et al (2020b) in Table 4B during the application of SAHPD for the drying of banana chips.…”
Section: Drying Kineticssupporting
confidence: 84%
See 3 more Smart Citations